PENINGKATAN HASIL BELAJAR MATERI BANGUN RUANG SISI LENGKUNG MENGGUNAKAN MEDIA BENDA ASLI - Ningtiyas, Susi Rahayu (Metafora: Education, Social Sciences and Humanities Journal, 2016)
The purpose of this study was to determine the improvement of student learning outcomes through the medium of learning the original object. This study uses research methods class 2 cycles, each cycle consisting of planning, implementation, observation and reflection. The subject of research SMP N 1 Paciran. Data were collected through observation, interviewing, and treatment of students. Based on observation, data showed on persiklus. The first cycle of the average value of 71.2 and 67.6% kertuntasan and the second cycle of the average value of 77.4 and 88.2% completeness. From this data, the researchers concluded that the original object learning media can improve students' mathematics learning outcomes SMP N 1 Paciran.